Insight into tribocorrosion resistance and tribofilm formation on titanium boride coatings in a phosphate buffer saline solution - B. Rahmatian; H.M. Ghasemi; M. Heydarzadeh Sohi; P. De Baets (Journal of Materials Research and Technology, 2023)
TiB2+TiB coatings were formed on Ti–6Al–4V through a molten-salt diffusional process at temperatures of 850 °C and 900 °C for 16 h. The thickness of the TiB layer increased by about two times at the higher process temperature, while the thickness of the TiB2 layer remained constant. Tribocorrosion rate of Ti–6Al–4V and the coated samples was evaluated in a reciprocating sliding under a normal load of 15 N in a phosphate buffer saline (PBS) solution for 3600–36000 cycles against an alumina ball. The results showed that the tribocorrosion rate of the borided samples decreased up to 56 times compared with Ti–6Al–4V after 36000 cycles. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) studies showed the presence of oxide-rich patches on the wear surface of Ti–6Al–4V with a thickness of up to 1 μm. TEM and atomic force microscopy (AFM) images also revealed the presence of a tribofilm with a thickness of up to 200 nm on the surface of the boride coating. In addition, X-ray photoelectron spectroscopy (XPS) analysis confirmed the tribofilm formed on the wear surface of coated samples contained B2O3/H3BO3 compound, resulting in a more stable fluctuation in coefficient of friction and open circuit potential during sliding. The SEM images of the alumina wear surface showed cracks and titanium transfer layers in contact with the borided layers and Ti–6Al–4V, respectively.